A critical historical exploration of the impact of black youth political activities on the community of Mogalakwena Local Municipality of Waterberg District in Limpopo Province, 1976-1994 - Marotola, Malesela Shadrack (My University, 2017)
This thesis focuses on youth political activities on the community of Mogalakwena Municipality, in the period 1976-1994. This period marks the intensity of the political struggle of black people against apartheid in the entire South Africa and Mogalakwena community in particular. The study reveals the youth as agents of change and catalysts in the struggle against apartheid in Mogalakwena. The study unpacks the factors that led to the mobilisation of the youth in Mogalakwena. It reflects on various factors such as the oppressive conditions of apartheid in South Africa and Lebowa in general. Above all, the study reveals that the banishment of Mosibudi Mangena of AZAPO to Mahwelereng in 1978 marked the beginning of conscious struggle in Mogalakwena. AZAPO became the bringboard of political mobilisation in Mahwelereng and the entire Mogalakwena Municipality. The study reveals the gradual assimilation of AZAPO members into UDF, which ultimately enabled the UDF to take the centre stage in the political in Mogalakwena. The period from 1980 to 1989 saw dramatic upsurge in youth political activities characterised by education, rent and consumer boycotts against the apartheid government. During this period, the community of Mogalakwena was engulfed by politics and gradually became politically aware. The study utilised its research questions properly and that made it easy to achieve its aim and objectives. As a result, the main research problem was addressed hence the impact of youth political activities in Mogalakwena was discovered. The study applied a purposive sampling and snowballing technique to identify informants. It further used both internal and external criticism to test the reliability of data from both oral and written sources. The use of the methodology stated above helped in selecting data to address the research problem. However, the study shows that more research can still be done on both political and economic aspects.
Thesis (PhD. (History)) -- University of Limpopo, 2017
Keywords: Black youth; Political activities; Mogalakwena Local Municipality; Youth -- Political activity -- South Africa; Apartheid